Substrate influence on tylosis formation when dogwood green cutting - Shapoval, A. (ТДАТУ, 2018)
The use of coconut fiber increases the chances of callus green cuttings development, when peat, on the contrary, inhibits and leads to rotting of the cuttings stem.
Keywords: substrate; artificially created climatic; garden; tylosis